2010
DOI: 10.1016/j.beproc.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of between-category similarity on basic level superiority in pigeons

Abstract: Children categorize stimuli at the basic level faster than at the superordinate level. We hypothesized that between-category similarity may affect this basic-level superiority effect. Dissimilar categories may be easy to distinguish at the basic level but be difficult to group at the superordinate level, whereas similar categories may be easy to group at the superordinate level but be difficult to distinguish at the basic level. Consequently, similar basic-level categories may produce a superordinate-before-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In addition, Lazareva, Soto and Wasserman (2010) showed that pigeons demonstrate a superordinate level categorization advantage if the basiclevel categories are similar, but the opposite pattern if the basic-level categories are very distinct. This suggests that the discriminability of different scene categories should be considered when making such comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lazareva, Soto and Wasserman (2010) showed that pigeons demonstrate a superordinate level categorization advantage if the basiclevel categories are similar, but the opposite pattern if the basic-level categories are very distinct. This suggests that the discriminability of different scene categories should be considered when making such comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…This chimpanzee also appeared to acquire the most abstract discriminations the most slowly, consistent with the idea that more abstract discriminations, in which exemplars share fewer perceptual features, should be the most difficult for nonverbal organisms to acquire. Within-category variance may have been more important than between-category variance for these chimpanzees (Lazareva et al, 2004;Lazareva et al, 2010). Although Marsh and MacDonald (2008) examined the features used by orangutans to perform concrete level discriminations, the factors underlying more abstract level concepts have yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given that very distantly related species, such as honeybees, have been shown to categorize at reasonably abstract levels (Benard, Stach, & Giurfa, 2006), the extent to which the process is an analogue to abstraction in humans has been questioned. Lazareva, Soto, and Wasserman (2010) have suggested that even abstract concepts may be readily discriminated because, although the exemplars within categories are perceptually diverse, there is also much greater variance and less overlap between the categories. The category discrimination tasks traditionally presented to pigeons and other animals may, therefore, allow even the more abstract categories to be discriminated on a perceptual basis (Vonk & Povinelli, 2012).…”
mentioning
confidence: 99%
“…Left-right reflection had no effect on pigeons' classification behavior, whereas top-bottom inversion, blurring, and quartering/scrambling of the photographs differentially impaired their categorization of natural and artificial stimuli. In addition, Lazareva, Soto, and Wasserman (2010) reported that betweencategory similarity affects the relative speeds of pigeons' learning basic-level and superordinatelevel tasks; these data may help to explain the occasionally contradictory results that have been reported in the developmental literature (e.g., Mandler & Bauer, 1988;Mareschal & Quinn, 2001;Oakes & Rakison, 2003;Rosch et al, 1976).…”
Section: Application Of the Paradigm To Superordinate Conceptsmentioning
confidence: 91%